THU0374 Vitamin D Levels and Effects of Vitamin D Replacement in Children with Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Cervical Adenitis (PFAPA) Syndrome. (10th June 2014) - Stagi, S.; Bertini, F.; Rigante, D.; de Martino, M.; Falcini, F.
Abstract : Background: The periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis (PFAPA) syndrome, is an autoinflammatory disease characterised by regularly recurrent fever episodes, due to seemingly unprovoked inflammation Objectives: To assess serum 25-hydroxy cholecalciferol (25(OH)D) concentrations in children with PFAPA and to evaluate longitudinally the effect of wintertime supplementation on 25(OH)D status and immune response in these children Methods: We have evaluated 25 Italian patients (19 males, 6 females, aged 2.4 - 5.3 years), fulfilled the Euro-Fever PFAPA criteria. For each patient, we recorded demographic and anthropometric data, clinical manifestations, serum calcium, phosphate, and 25(OH)D. After 400 UI 25(OH)D supplementation, clinical and auxological characteristics, calcium and phosphate, and 25(OH)D) concentrations were re-evaluated. Data was compared with a sex- and age-matched control group Results: PFAPA patients showed very reduced 25(OH)D levels than controls (p<0.0001). Regarding the effect of the different seasons on 25(OH)D status, 25(OH)D levels in winter were significantly reduced respect the summer (p<0.005). These values are significantly lesser than controls (p<0.005). However, 25(OH)D levels correlated with episodes of fever (p<0.005), and CRP (p<0.005). After vitamin D3 supplementation, PFAPA patients disclosed significantly increased 25(OH)D levels, showing a significative reduction of febrile episodes and his characteristics (mean duration of fever episodes p<0.05, number of febrile episodes for year p<0.005) Conclusions: Deficient and insufficient vitamin D serum levels were found in most children with PFAPA. Hypovitaminosis D can be significant risk factor for PFAPA occurrence. However, After 25(OH)D supplementation seems significantly to reduce PFAPA episodes and fever duration, disclosing the importance of vitamin D as immunoregulatory factor in this syndrome Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4630